The Unfinished Revolution : Bringing Opportunity, Good Jobs and Greater Wealth to All Tunisians - World Bank (Washington, DC, 2014)
Until 2010 Tunisia appeared to be doing well and was heralded by the World Bank and the IMF as a role model for other developing countries, and the World Economic Forum repeatedly ranked Tunisia as the most competitive economy in Africa. Yet, the Tunisian model had serious flaws. Inadequate creation of jobs, notably for university graduates, and deep regional disparities were a source of increasing frustration across the country in the run up to the January 2011 Revolution. This development policy review shows that, in contrast to the façade often presented by the former regime, Tunisia's economic environment was and remains deeply deficient. The review highlights an economy that has remained frozen in low-value added activities and where firms are stagnating in terms of productivity and jobs creation. The review argues that Tunisian prosperity has been held back by policies that have reduced the country s overall economic performance. This poor performance results from extensive barriers to entry and market restrictions coupled with a heavy business regulations and a poorly functioning financial system, have resulted in economic stagnation. Economic policies have exacerbated cronyism and rent-seeking, allowing under-performing firms to survive, regardless of their productivity. in order to fulfill its economic potential, Tunisia needs to create a level playing field by opening up the economy and removing Tunisia's three dualisms, namely the onshore-offshore division, the dichotomy between the coast and the interior, and the segmentation of the labor market. A strong social policy is also necessary, of course, and should be designed to accompany private sector-led growth. Tunisia can capitalize on a strong competitive advantage to export wage-intensive goods, expand its export of services, and unleash the potential of agriculture, to the benefit of small businesses, young graduates, and farmers in Tunisia's long-neglected interior regions. Realizing these benefits will require improving the investment climate, rationalizing regulations, and developing more equitable development policies that benefit all of Tunisia's regions. The Unfinished Revolution is a challenge for policymakers to rethink Tunisia's economic development model, to question existing assumptions, and to dare to think big about policy reforms which can accelerate growth and shared prosperity, create quality jobs and promote regional development.